2020
DOI: 10.7759/cureus.7319
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Response to Recombinant Growth Hormone Therapy on Height Gain in Patients with Idiopathic Short Stature Vs. Patients with Growth Hormone Deficiency

Abstract: The use of recombinant human growth hormone (rhGH) in patients with idiopathic short stature (ISS) has been an area of concern since some studies reported less desired effects of the drug in this group of patients as compared to patients with growth hormone deficiency (GHD). In addition, there were no studies addressing the effects of rhGH in Saudi children. Therefore, we conducted a retrospective study to observe the effects one year of treatment with rhGH on the mean height gain in patients with ISS and GHD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…In this study, the mean age before starting GH therapy was 12.55 years, the mean initial bone age was 9.27 years (delayed), the mean initial height SD was − 3.42 SD, the mean initial weight SD was − 2.65 SD, and the mean mid-parental height SD was − 0.97 SD. These results were comparable to those of Alzahrani et al [ 16 ] where mean age was 10.77 years ± 2.48 and the mean initial height was 125.35 cm ± 11.72.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the mean age before starting GH therapy was 12.55 years, the mean initial bone age was 9.27 years (delayed), the mean initial height SD was − 3.42 SD, the mean initial weight SD was − 2.65 SD, and the mean mid-parental height SD was − 0.97 SD. These results were comparable to those of Alzahrani et al [ 16 ] where mean age was 10.77 years ± 2.48 and the mean initial height was 125.35 cm ± 11.72.…”
Section: Discussionsupporting
confidence: 91%
“…These results were similar to the results of Quitmann et al [ 1 ] with mean height SD after 1 year treatment − 2.06 SD in the ISS group, − 1.91 SD in the GHD group (best response), and − 2.05 SD in the SGA group. However, Alzahrani et al [ 16 ] found no significant differences in height gain after treatment between the GHD and ISS groups.…”
Section: Discussionmentioning
confidence: 99%
“…7 This was consistent with the fact that the dose of GH for patients with ISS approved by the FDA (2003) was generally 0.15 2 GV changes after rhGH treatment, the error bar represents standard deviation. 15 From the start of and up to two years of treatment, the rhGH dose was significantly higher in the ISS group compared with the GHD group. With the extension of the rhGH treatment time, the GV of the two groups at the second year of treatment was lower than at the first but the difference between the ISS and GHD groups was not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…An existing study revealed that following rhGH treatment for ISS, the treatment response indicated a significant dose-dependent pattern, where a higher unit dose was more effective than a lower unit dose. 14 Alzahrani et al 15 retrospectively analyzed 110 children (76 with GHD and 34 with SGA). Their research considered the starting age, treatment time, and treatment dose as the main influencing factors on growth rate.…”
Section: Discussionmentioning
confidence: 99%